Management of Bladder Cancer following Solid Organ Transplantation - Jeffrey J. Tomaszewski; Jeffrey A. Larson; Marc C. Smaldone; Matthew H. Hayn; Stephen V. Jackman (Advances in Urology)
Objective. Present our experience managing bladder cancer following liver and renal transplantation. Methods. Single institution retrospective review of patients diagnosed with bladder urothelial carcinoma (BUC) following solid organ transplantation between January 1992 and December 2007. Results. Of the 2,925 renal and 2,761 liver transplant recipients reviewed, we identified eleven patients (0.2%) following transplant diagnosed with BUC. Two patients with low grade T1 TCC were managed by TURBT. Three patients with CIS and one patient with T1 low grade BUC were treated by TURBT and adjuvant BCG. All four are alive and free of recurrence at a mean follow-up of 51 ± 22 months. One patient with T1 high grade BUC underwent radical cystectomy and remains disease free with a follow-up of 98 months. Muscle invasive TCC was diagnosed in four patients at a median of 3.6 years following transplantation. Two patients are recurrence free at 24 and 36 months following radical cystectomy. Urinary diversion and palliative XRT were performed in one patient with un-resectable disease. Conclusions. Bladder cancer is uncommon following renal and liver transplantation, but it can be managed successfully with local and/or extirpative therapy. The use of intravesical BCG is possible in select immunosuppressed patients.